Integration of Digital Literacy in PAI Learning in the 5.0 Era at SMKN 3 Cilegon - Eti Shobariyah; Ali Yakub; Wasehudin Wasehudin; Sayuti Sayuti; Romi Maimori (Ta'dib, 2026)
The acceleration of digital technology demands adaptation of education in the era of Society 5.0, including in Islamic Religious Education (PAI) learning, which still tends to be conventional. At SMKN 3 Cilegon City, the utilization of digital literacy in improving the quality of learning is not optimal. Digital literacy encompasses not only technical skills, but also critical, ethical, creative, and productive skills. This study aims to analyze the integration of digital literacy in PAI learning to improve the quality of student learning. The method used is descriptive qualitative with students of SMKN 3 Cilegon City as subjects. Data analysis uses an interactive model through the stages of reduction, presentation, conclusion and verification of conclusions. The results show that the integration of digital literacy is carried out through the use of technology in learning, project-based implementation, strengthening the role of teachers as facilitators, and the use of technology for personalized learning, which overall contribute to improving the quality of learning.